Experimental evaluation of aluminothermic welds - Lukáš Zeman; Jaroslav Valach; Petr Zlámal; Nela Krčmářová; Veronika Koudelková; Jaroslav Zeman (Acta Polytechnica CTU Proceedings, 2023)
The article presents a study of the mechanical processes occurring during the aluminothermic reaction using experimental methods (strain gauges, digital image correlation, thermography, scanning electron microscopy, profilometry). The aluminothermic reaction is a highly efficient welding method due to its exothermic behaviour, however, it places considerable demands not only on the welding technique, but also on the capabilities of the experimental methods used; these limitations are also discussed in the article. The aluminothermic reaction is associated with the formation of a localised heat source with a time evolution dictated by the technological procedure, which manifests itself in heat propagation to the surrounding weld material. The unequal evolution of the temperature field is the fundamental cause of the appearance of the heat affected zone or local deformations or surface curvature, which was the focus of the experimental methods deployed above and the results of which are shown in the article.